ICTV Virus Taxonomy Profile: Potyviridae 2022 - Inoue-Nagata, A.K.; Jordan, R.; Kreuze, Jan F.; Li, F.; López Moya, J.J.; Mäkinen, K.; Ohshima, K.; Wylie, S.J. (Microbiology Society, 2022)
The family Potyviridae includes plant viruses with single-stranded, positive-sense RNA genomes of 8–11 kb and flexuous filamentous particles 650–950 nm long and 11–20 nm wide. Genera in the family are distinguished by the host range, genomic features and phylogeny of the member viruses. Most genomes are monopartite, but those of members of the genus Bymovirus are bipartite. Some members cause serious disease epidemics in cultivated plants. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Potyviridae, which is available at ictv.global/report/potyviridae.